Reclamation of saline-alkali soils in Xinjiang: A review - LYU Ning; SHI Lei; DAI Yuyu; LI Yunxia; YIN Feihu (Guan'gai paishui xuebao)
Saline-alkali soils in Xinjiang are extensive and diverse. Reclaiming these soils for agricultural production plays a critical role in safeguarding food security in China. Exploring reclamation technologies that align with the arid environmental nature and modern water-saving irrigation techniques unique in the region is crucial for the sustainable use of these saline-alkali soils. This paper reviews the historical development and effectiveness of various saline-alkali soil management techniques in Xinjiang, based on literature review and quantitative evaluation of available data. We analyze the bottlenecks in managing saline-alkali soils under the constraints of limited water resources, providing insight into comprehensive utilization strategies for saline-alkali soils in the context of new challenges faced by the region. Based on the balance between water and soil resources, as well as the characteristics of secondary soil salinization in irrigated farmland, we propose an integrated ‘prevention, control, and treatment’ strategy for soil management in watersheds and irrigation districts in the region. Our recommendations include determining rational water resource allocation for irrigation and ecological maintenance, identifying effective techniques to desalinate specific soil layers in drip-irrigated farmlands, establishing dynamic monitoring systems to monitor soil salinization, and implementing prevention-control measures tailored to different types of salinized soils in different areas in the region. These provide a guidance for policymaking to improve management and utilization of saline-alkali soils in Xinjiang.